Lichen Simplex Chronic Skin Problems in Diabetes Mellitus Patient: A Case Report - Nur Aida Oktasari; Najmarani Devi Firdaus; Ade Firman Saroso (Archives of The Medicine and Case Reports, 2023)
Diabetes mellitus is an endocrine, metabolic disease that can occur in all ages and socioeconomic groups. Uncontrolled diabetes mellitus can cause various complications. One of them is the manifestation of the skin. Chronic lichen simplex in diabetes mellitus patients was reported in cases with uncontrolled blood sugar levels greatly affecting chronic skin lesions in patients. Controlled sugar levels and appropriate topical therapy and psychological management in patients are expected to provide better output and prognosis. The patient came with complaints of itchy, red and painful wounds on both legs, accompanied by a fever for 7 days, Previously the patient often had numbness and tingling in the upper and lower extremities. Patients often scratch their skin, resulting in wounds that then dry out and thicken. The patient also has the comorbid disease of Diabetes mellitus. Complaints have been recurring frequently and have been felt for more than the last 2 years. Itching often recurs, especially when you think about something a lot and when you are resting. Based on the dermatological examination, the results showed that on both lower limbs, there were non-layered smooth white scaly lesions, lichenification accompanied by hyperpigmentation, the size of the plaques had indistinct boundaries, there was slight edema and erythema, multiple erosions with black crusts on the surface of the lesion were not easily removed. Diabetes mellitus is associated with dermatologist disorders. Early recognition of initial cutaneous changes such as xerosis, hyperkeratosis, or skin infections by appropriate management could help reduce late or severe complications of diabetes. Although most dermatological conditions require specific treatment, the most important rule is to improve blood glucose levels control in patients. Education in treatment, hygiene, emotional stress and lifestyle changes are important for improving the quality of life for patients with diabetes mellitus.